PERBEDAAN KARAKTERISTIK TUBUH MERPATI TINGGI JANTAN DAN MERPATI BALAP JANTAN LOKAL - Fery Efata Zebua; Rr. Riyanti; Tintin Kurtini (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
This study aims to 1) describe the different characteristics of racing pigeons and doves male high (eye color, fur color, head shape, and the shape of the body). 2) identifying differences in the characteristics of high male pigeons and racing pigeons male). The research was conducted in December 2015 in captivity and pigeon racing pigeons high on the road abdinegara number 43 Sumur Batu, Teluk Betung and Pagar Alam road number 49, Tanjung Karang Barat, Bandar Lampung. This study used survey method with the observation of qualitative and quantitative characteristics. The results showed qualitative characteristics at high male pigeons dominated by the color of the yellow, the color of feathers tritis, rounded head shape and body shape banana. As for the male pigeon racing is dominated by the color of the iris yellow, Prumpung coat color, head shape turtledove, and body shape banana. High pigeon males have an average length of beak 2,53 ± 0,50 cm longer and shorter body weight ie 331,32 ± 15,36 gr compared to males racing pigeons which have a longer half-life 2.46 ± 0,50 cm and weight 444,03 ± 55,31 gr and wide flutter higher saayap namely 28,93 ± 1,08 cm compared to the racing pigeons 25.16 ± 0,79 cm and length leg lower 8,46 ± 1,30 cm than racing pigeons cm 14.93 ± 0,86 cm. Keywords: Characteristics, Qualitative and Quantitative, Columba Livia Local Male